For konge og fædreland: Valdemar Sejr hos B.S. Ingemann og Agnes Slott-Møller - Møller, Lis (Passage - Tidsskrift for litteratur og kritik, 2019)
Lis Møller: “For King and Fatherland – King Valdemar the Victorious in works by B.S. Ingemann and Agnes Slott-Møller” This article offers a comparative reading of two fictionalized renditions in two different media of the Danish king Valdemar the Victorious (1170-1241): B.S. Ingemann’s historical novel Valdemar Seier (1826) and Agnes Slott-Møller’s cycle of historical paintings Valdemar Sejr (1927-1934). Focusing on Ingemann’s and Slott-Møller’s medievalism and their views on the nature and function of historical fiction and historical painting, respectively, the article argues that the two representations of King Valdemar are in fact compatible. What sets them apart is the historical context.